Determinant of Financial Management Behavior and Impact on Financial Satisfaction in Generation Z - Nurul Azizeh; Umi Widyastuti; Muhammad Yusuf (JURNAL DINAMIKA MANAJEMEN DAN BISNIS, 2022)
The purpose of this study is to determine the factors that influence the behavior of financial management. This study was conducted in the Jakarta area with a sample of Generation Z with age range between 17-27 years as many of 325 respondents. Sampling technique using convenience sampling, while research analysis technique with SEM (Structural Equation Model) using AMOS software. The results showed that financial knowledge has a significant influence on financial attitude, financial attitude significantly has an influence on financial management behavior, financial attitude has no influence on financial satisfaction, financial knowledge significantly has an influence on financial management behavior, financial knowledge has no influence on financial satisfaction, and financial management behavior significantly has an influence on financial satisfaction.